Compiler-directed scratch pad memory optimization for embedded multiprocessors. - Kandemir, M. (IEEE Transactions on VLSI systems)
This paper presents a compiler strategy to optimize data accesses in regular array-intensive applications running on embedded multiprocessor environments. Specifically, we propose an optimization algorithm that targets at reducing extra off-chip memory accesses caused by interprocessor communication. This is achieved by increasing the application-wide reuse of data that resides in scratch-pad memories of processors. Our results obtained using four array-intensive image processing applications indicate that exploiting interprocessor data sharing can reduce energy-delay product significantly on a four-processor embedded system.